Major pitfalls of protein kinase inhibitors prescription: A review of their clinical pharmacology for daily use. (September 2019) - Gougis, Paul; Palmieri, Lola-Jade; Funck-Brentano, Christian; Paci, Angelo; Flippot, Ronan; Mir, Olivier; Coriat, Romain
Abstract: Protein kinase inhibitors (PKI) are a growing class of anticancer agents. They are prescribed with flat doses, and their oral administration is associated with interindividual variability in exposure. Patients can be over- or underexposed, due to numerous factors. We reviewed key pharmacokinetic concepts and mechanisms by which PKIs prescription could be altered. Challenging situations that could lead to increased toxicity or to therapeutic failure are described and recommendation for clinicians are proposed. Finally, the interest of therapeutic drug monitoring and indications for its use in daily practice is discussed.